(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the problem of translating culture-bound words and the most preferred methods of translating realia from Uzbek into English. The article discusses types of words that have no alternative in translation, classifications and proposed methods of translating realia. To support the opinions expressed in the article, quotes are provided from the scientific works of researchers. The purpose of the research covered in the article is to study and analyze the means of translating words and phrases characteristic of the Uzbek linguistic culture into English, as well as to determine the most optimal translation methods for carrying out reliable translation. On conducting the research in the article, there were used such linguistic methods as method of linguistic observation and description, comparison and contrast. As a conclusion, the idea of using the most successful and acceptable methods based on a comparative analysis of translation samples in individual cases is put forward due to the fact that it is impossible to create general rules for translating existing realia in the Uzbek language.